PENGARUH DISIPLIN KERJA DAN PENGAWASAN TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KABUPATEN MUSI RAWAS - Dheo Rimbano; Yuli Efrianti; Yunita Yunita (Jurnal Media Ekonomi (JURMEK), 2018)
This research was conducted at the Social Service Office of Musi Rawas Regency with the aim of research to determine the effect of work discipline and supervisors on employee performance partially. This type of research used quantitative methods of data sources used primary data, data collection techniques used questionnaires with research respondents as many as 44 employees. Data analysis techniques used simple linear regression, test the correlation coefficient and t test. multiple linear regression, test the coefficient of determination and F test. the test results show that the effect of work discipline on employee performance in the Social Service of Musi Rawas Regency shows that the level of the relationship coefficient is strong. The partial test (t test) of the tcount of 11.426 and ttable of 1.684 shows that there is an influence of work discipline on employee staff at the Musi Rawas District Social Service.Effects of Supervision on Employee Performance at the Social Service of Musi Rawas Regency. X, the value of R or Multiple R is 0.530 indicating that the level of the relationship coefficient is strong. Partial test (t test) value of tcount of 13.522 and t table of 1.684 that there is an influence of supervision on the performance of employees at the Social Service Office of Musi Rawas Regency. + b2X2, the regression equation is Y = 43.236 + 0.735X1 + 0.340X2. R2 value is 0.631 means that the determination coefficient value is 0.631, the level of relationship is included in the medium category. Test F value of F count is 35.041 and Ftable is 3.230, there is the influence of work discipline and supervision of employee performance at the Social Service of Musi Rawas Regency.